A new karyotype of Calomys (Rodentia, Sigmodontinae) - Lima, J. Fernando de S.; Kasahara, Sanae [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2001)
The genus Calomys Waterhouse, 1837 is widely distributed within South America, being found in Venezuela, Colombia, Peru, Bolivia, Brazil, Paraguay, Uruguay and Argentina. Specimens of Calomys were collected in Formoso do Araguaia, Tocantins, Brazil. For chromosome characterization standard staining techniques and as G-banding and nucleolar organizer region were used. The karyotype was 2n=46 and AN=66. The X chromosome is a medium metacentric and the Y chromosome a small acrocentric chromosome. Chromosome homologies with other species were observed. Probably, karyotype differences were basically due to Robertsonian rearrangements.
Keywords: Calomys; karyotype; chromosome; Tocantins; Brazil